Comparison of postoperative bleeding using harmonic scalpel and LigaSure in thyroid surgery: a 15-year single-centre retrospective study - Francesk Mulita; George Theofanis; Georgios-Ioannis Verras; Elias Liolis; Vasileios Papanikos; Levan Tchabashvili; Konstantinos Tasios; Fotios Iliopoulos; Christos Tsilivigkos; Dimitrios Kehagias; Charalampos Kaplanis; Andreas Antzoulas; et al. (Medicinski glasnik, 2023)
Aim: Thyroidectomy is the most common operation in the field of endocrine surgery. The aim of this study was to compare the use of LigaSure vessel (LS) and harmonic scalpel (HS) in 1653 total thyroidectomies between January 2008 and March of 2023, with regards to analysis of surgical bleeding complications duration the hospital stay and operative surgical time. Methods: It is a retrospective analysis of a prospectively maintained database. Patients have been categorized into two groups: Group A included 718 patients from January 2008 to May 2013 when LS was used, and the Group B included 935 patients from June 2013 to March 2023 when HS was used. Results: From the total of 14 postoperative bleeding cases that occurred in patients of Group A, only in 4 of them it was necessary to have a reoperation. The other 10 cases involved minor haemorrhages, while from the total of 6 postoperative bleeding cases that happened to patients of Group B, there were 4 cases that needed a reoperation (p-value >0.05) and 2 patients with minor haemorrhages. The postoperative evaluation of minor bleedings revealed statistically significant differences between the two groups (p-value < 0.05). The average hospital stay was similar in the two groups. Conclusion: Both devices exhibit identical safety profiles in thyroidectomies specifically regarding major bleeding complications that require reoperation. Additionally, HS was found to be more effective at achieving haemostasis, especially in the subgroup of patients with thyroid carcinoma. The results of the present study may be useful for high-volume centres performing numerous thyroidectomies every day.
Keywords: bleeding; complications; LigaSure; thyroidectomy; UltraCision